Professional education in contemporary Serbia: an examination of the intellectual transition from state-socialism to post socialism - Kaurin, Dragoljub (2012)
The thesis, professional education in contemporary Serbia, an examination of the transition from state-socialism to post-socialism tries to answer the question of the changing patterns of professional education in contemporary Serbia in the light of the advent of post-socialism, after a very long period of reign of state-socialism. It does so by employing an in-depth historical analysis. It is argued that the economic problems in post-socialism, blocked transformation, exclusion from the European Community, and other problems impacted on the change in professional education patterns. Post-socialism is distinguished by the growing marketization, globalization and the economic intra-dependence, as well as the stronger influence of the emerging markets. In Serbia, it is distinguished by the fragile economic recovery and the emergence of the new economic order. The thesis uses Antonio Gramsci’s concept of hegemony to explain the inevitability of the knowledge economy and Karl Popper’s theoretical concepts developed in his study Open Society and its Enemies. Methodologically, the project used chiefly qualitative methodology: questionnaires, interviews and focus group discussions. In addition to this, there is also abundant use of the relevant documents, useful for documentary analysis, as well as biographical method. Empirical conclusions of the project are based on 5 months survey in contemporary Serbia, based on qualitative methodology, and participants were university teachers, lawyers and researchers. Survey is understood here as a social science research technique.